KAJIAN UNDANG-UNDANG OTONOMI DAERAH TERHADAP PERSOALAN BATAS WILAYAH - Abdul Choliq Dahlan (Jurnal Pembaharuan Hukum, 2014)
Regional autonomy laws either in Law No. 22 of 1999 Section 89 and as successor Act No. 32 of 2004 still contains many flaws that eventually lead to problems many disputes betweenregions, especially special again raises the issue of boundaries. Thus certainly necessary legal product that is able to provide answers and be able to prevent the emergence of inter- regional disputes in this case the author is more likely in the form of laws rather than laws under law because the issues emerging boundaries often cause many problems such as political, economic, culture, religion, race and so forth. From the findings obtained Nurbadri important point that conflict boundaries between regions mainly influenced by the legal and non- legal factors. Legal factors have two (2) legal substance that is first caused by the formation of legislation that are too hasty, the blurring of the boundary setting, and secondly the lack of socialization Act of regional expansion. The next is not yetclear legal structure due to changes in legislation that is too short.